2017
DOI: 10.26480/mjsa.02.2017.09.11
|View full text |Cite
|
Sign up to set email alerts
|

Rainwater Harvesting System: Low Awareness Level Among University Students in a High Rainfall Tropical Country

Abstract: Water scarcity has emerged as a global issue and the situation is getting worse. In accordance with the urgency, this study aimed to assess the suitability of a rainwater harvesting system (RWHS) to supply water for domestic uses in residential colleges in the Bangi campus of Universiti Kebangsaan Malaysia (UKM). The study also analysed the level of awareness on the importance of rainwater and RWHS among the students residing in the 10 residential colleges. The study used Likert scale 1 -5 questionnaire survey… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 4 publications
0
7
0
Order By: Relevance
“…have mean values lower than 4.00. According to a study, harvested rainwater usually used as a domestic storage for washing cars, plants watering and for laundry [5]. Their study found that most people has low willingness to use harvested rainwater for shower and cooking due to the fact that rainwater have not undergo proper treatment which can make it safe to consume.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…have mean values lower than 4.00. According to a study, harvested rainwater usually used as a domestic storage for washing cars, plants watering and for laundry [5]. Their study found that most people has low willingness to use harvested rainwater for shower and cooking due to the fact that rainwater have not undergo proper treatment which can make it safe to consume.…”
Section: Resultsmentioning
confidence: 99%
“…Their study found that most people has low willingness to use harvested rainwater for shower and cooking due to the fact that rainwater have not undergo proper treatment which can make it safe to consume. However, they also explained that the respondents are willing to use harvested rainwater for external use [5]. For example, using harvested rainwater for toilet cleaning and floor mopping.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The majority of coals in Xishanyao formation belong to the range of medium-extra low sulfur, part of which are high-sulfur coal (Qinping et al 2012, Shuxun et al 2001, Tan et al 2017. The macrolitho type of coal focuses on semibright type and semidull type.…”
Section: Geological Backgroundmentioning
confidence: 99%
“…As for the services of the Ministry of Water Resources, determination of RT has already been started at the village level. The mountainous areas account for almost two thirds of China's total land area , Tan et al 2017. In addition, the small basis in mountainous areas are often ungauged, as they are short of monitoring facilities.…”
Section: Introductionmentioning
confidence: 99%